Cannabinoid‐1 Receptor Antagonism Improves Glycemic Control and Increases Energy Expenditure Through Sirtuin‐1/Mechanistic Target of Rapamycin Complex 2 and 5′Adenosine Monophosphate–Activated Protein Kinase Signaling. Issue 4 (6th March 2019) - Liu, Jie; Godlewski, Grzegorz; Jourdan, Tony; Liu, Ziyi; Cinar, Resat; Xiong, Keming; Kunos, George
Abstract : Endocannabinoids promote energy conservation in obesity, whereas cannabinoid‐1 receptor (CB1 R) blockade reverses body weight gain and insulin resistance and increases energy expenditure. Here we investigated the molecular mechanisms of the catabolic effects of CB1 R blockade in the liver. Exposure of primary mouse hepatocytes and HepG2 cells to the CB1 R agonist arachidonyl‐2'‐chloroethylamide inhibited the expression of Sirtuin‐1 (Sirt1) and Rictor, a component of mechanistic target of rapamycin complex 2 (mTORC2) and suppressed insulin‐induced Akt phosphorylation at serine 473. These effects were reversed by peripheral CB1 R antagonist JD5037 in control hepatocytes but not in hepatocytes deficient in Sirt1 and/or Rictor, indicating that these two proteins are required for the CB1 R‐mediated inhibition of insulin signaling. Feeding C57BL/6J mice a high‐fat diet (HFD) inhibited hepatic Sirt1/mTORC2/Akt signaling, and the inhibition was reversed by rimonabant or JD5037 in wild‐type but not liver‐specific Sirt1 ‐/‐ (Sirt1‐LKO) mice, to levels observed in hepatocyte‐specific CB1 R ‐/‐ mice. A similar attenuation of hyperglycemia and hyperinsulinemia in wild‐type mice with obesity but not in Sirt1‐LKO mice could be attributed to insufficient reversal of HFD‐induced mitochondrial reactive oxygen species generation in peripheral tissues in the latter. In contrast, JD5037 treatment was equally effective in HFD‐fed wild‐type and Sirt1‐LKO mice in reducing hepatic steatosis, increasing fatty acid β‐oxidation, and activating 5′adenosine monophosphate–activated protein kinase (AMPK) through liver kinase B1 (LKB1), resulting in a similar increase in total energy expenditure in the two strains. Conclusion: Peripheral CB1 R blockade in mice with obesity improves glycemic control through the hepatic Sirt1/mTORC2/Akt pathway, whereas it increases fatty acid oxidation through LKB1/AMPK signaling.